Knotting of Percutaneous Endoscopic Jejunostomy Feeding Tubes in Two Patients with Parkinson’s Disease and Continuous Duodopa® treatment - Krones, E.; Zollner, G.; Petritsch, W. (Zeitschrift für Gastroenterologie, 2012)
Continuous intraduodenal infusion of levodopa/carbidopa (Duodopa®) via PEJ tubes is increasingly used in patients with advanced stages of Parkinson’s disease. Tube-related complications such as kinking or coiling have been frequently reported. We herein describe two cases of tube dysfunction in patients with Parkinson’s disease and continuous Duodopa® treatment due to knotting of the distal end of the tube. The mechanisms of knotting are unclear although a causative role of impaired gastrointestinal motility either by Parkinson’s disease itself or Duodopa® treatment might be suspected.
Keywords: PEJ tube; tube dysfunction; Parkinson’s disease; Duodopa